2019
DOI: 10.1051/epjconf/201921406028
|View full text |Cite
|
Sign up to set email alerts
|

Deployment of a Matrix Element Method code for the ttH channel analysis on GPU’s platform

Abstract: The observation of the associated production of the Higgs boson with two top quarks in proton-proton collisions is one of the highlights of the LHC Run 2. Driven by the theoretical description of the physics processes, the Matrix Element Method (MEM) consists in computing a probability that an event is compatible with the signal hypothesis (ttH) or with one of the background hypotheses. It is a powerful classifying tool requiring high dimensional integral computations. The deployment of our MEM production code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…All the parton combinations are described by the Σ p term and σ i is a normalization factor tuned to achieve the best signalto-background separation when combining the weights into a likelihood ratio. The computation of these weights are CPU intensive and a GPU-based derivation has been proposed successfully [3]. An excess has been observed with respect to the background-only hypothesis in the multilepton final states: 3.2σ observed significance (2.8σ expected) [2].…”
Section: The Matrix Element Methods Used On 2016 Lhc Run II Datamentioning
confidence: 99%
“…All the parton combinations are described by the Σ p term and σ i is a normalization factor tuned to achieve the best signalto-background separation when combining the weights into a likelihood ratio. The computation of these weights are CPU intensive and a GPU-based derivation has been proposed successfully [3]. An excess has been observed with respect to the background-only hypothesis in the multilepton final states: 3.2σ observed significance (2.8σ expected) [2].…”
Section: The Matrix Element Methods Used On 2016 Lhc Run II Datamentioning
confidence: 99%
“…Many developments have been made recently in the context of the MEM by using either parallel computing [22,23] or GPU acceleration [24,25]. In addition methods that bypass the classic numerical integration libraries by using boosted decision trees [26] or neural networks [27], and the recent new applications of normalizing flows for phase-space sampling [28,29] are promising ways to improve the computation time and potentially to avoid the currently required integration variables optimizations such as implemented in MoMEMta.…”
Section: Jhep04(2021)020mentioning
confidence: 99%
“…In the past, several conceptual studies have shown substantial performance gains, both for tree-level computations [27][28][29][30][31][32][33][34][35][36] and for one-loop level computations [37,38]. In addition, the evaluation of PDFs [39] and the matrix element method [40][41][42] have been explored on GPUs. Nevertheless, a production-ready GPU-enabled event generator suitable for experimental applications has not yet become available.…”
Section: Introductionmentioning
confidence: 99%